Preparation of a N, S, P co-doped and oxidized porous carbon for the efficient adsorption of uranium(VI) - Liu, Yan (2023)
A N, S, P co-doped and oxidized porous carbon was prepared by the carbonization of poly (cyclotriphosphazene-co-4,4'-sulfonyldiphenol) at 750 ℃, followed by KOH activation and HNO3 oxidation. The carbon was used as an adsorbent for uranium(VI) in aqueous solutions. TEM, SEM, XPS and FTIR were used to characterize its microstructure before and after adsorption. Results indicate that there is an optimum pH value of 6 for U(VI) adsorption. The adsorption kinetics and isotherms were fitted well by the pseudo-second-order and the Langmuir models, respectively. The maximum adsorption capacity determined by the Langmuir model at 298 K and a pH value of 6 was 402.9 mg g−1. The carbon has excellent reusability and retains 70% of the capacity of the original value after five adsorption-desorption cycles. The high U(VI) adsorption capacity is mainly attributed to the carboxyl, and P and S groups by the formation of the UO22+(COO−)2 complex, and U-O-P and U-O-S bonds.